Survey of Students' Interest in Participating in Swimming Extracurricular Activities - Moch. Irfan Rifa’i; Wasis Himawanto; Ruruh Andayani Bekti; Rizki Burstiando Rizki Burstiando (Sriwijaya Journal of Sport, 2024)
This research aims to see how interested students are in taking part in extracurricular swimming activities. The method used by researchers is a survey method using a questionnaire. By using the survey method, data can be obtained which will be analyzed using descriptive and percentage statistical techniques. Based on the results of the research and discussion, the following conclusions can be drawn from this research: Students' interest in participating in extracurricular swimming activities in elementary schools from the overall data tends to be in the High category. Students' interest in participating in extracurricular swimming activities in elementary schools from the overall data tends to be in the High category. In this category, student interest was very high, accounting for 12 students (26.67%), in the high category, accounting for 13 students (28.89%), in the sufficient category, accounting for 9 students (20%), and in the low category. a total of 11 students (24.44%). The results of the implications used in this research provide input for schools to create better extracurricular swimming programs.